2005
DOI: 10.1152/ajpcell.00420.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the immunoexpression of aquaporin 9 by ovarian hormones in the rat oviductal epithelium

Abstract: Brañ es, María C., Bernardo Morales, Mariana Ríos, and Manuel J. Villalón. Regulation of the immunoexpression of aquaporin 9 by ovarian hormones in the rat oviductal epithelium. Am J Physiol Cell Physiol 288: C1048 -C1057, 2005. First published January 12, 2005; doi:10.1152/ajpcell.00420.2003.-The volume of oviductal fluid fluctuates during the estrous cycle, suggesting that water availability is under hormonal control. It has been postulated that sexsteroid hormones may regulate aquaporin (AQP) channels invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…The increased oviductal fluid secretion is mostly due to the increased water availability, which is related to the function of the transmembrane water transport proteins, aquaporins (AQPs). In rats, expression of Aqp5, Aqp8 and Aqp9 is regulated by both E 2 and P 4 (Branes et al 2005). These findings indicate that E 2 , P 4 and prolactin play a major role in fluid production in the oviduct.…”
Section: Tubal Fluid Flowmentioning
confidence: 74%
“…The increased oviductal fluid secretion is mostly due to the increased water availability, which is related to the function of the transmembrane water transport proteins, aquaporins (AQPs). In rats, expression of Aqp5, Aqp8 and Aqp9 is regulated by both E 2 and P 4 (Branes et al 2005). These findings indicate that E 2 , P 4 and prolactin play a major role in fluid production in the oviduct.…”
Section: Tubal Fluid Flowmentioning
confidence: 74%
“…In addition, studies found that AQP9 was the only AQP localized after ovariectomy and administration of progesterone and estradiol (Branes et al, 2005). These results indicate that AQPs function not only in water transport but also in the absorption or secretion of luminal fluid metabolites, thus maintaining a suitable environment for reproductive functions (Kenny et al, 2002).…”
Section: Female Reproductive Systemmentioning
confidence: 82%
“…In the literature thus far, there are two reports pertaining to AQP localization in oviductal tissues. Branes et al (2005) showed by IHC the expression of AQP5, AQP8, and AQP9 in the epithelial cells of the rat oviduct. In turn, Gannon et al (2000) found AQP1 labeling in the innermost and the inner cells of the circular muscular layer of the rat oviduct.…”
Section: Aqps In Oviductmentioning
confidence: 96%